EFFECT OF PARENTS’ OCCUPATION AND EDUCATIONAL BACKGROUND ON STUDENTS’ ACADEMIC PERFORMANCE IN SECONDARY SCHOOLS IN ANAMBRA STATEEffect of Parents’ Occupation and Educational Background on Students’ Academic Performance in Secondary Schools in Anambra State - Ogechukwu , Okoye Faith; Innocent, Ogbu Sunday (International Journal For Research In Business, Management And Accounting, 2020)
The study investigated effects of parents’ occupation and educational background on students’ academic performance in Secondary Schools in Anambra State. Three research questions guided the study. Descriptive survey design was adopted. A sample of 884 senior secondary school students in form two (SS2) was drawn from the population of 2945 using proportionate stratified random sampling technique. Simple random sampling technique was employed in the choice of schools for the study. Instrument for data collection was questionnaire, validated by three experts, two from Departments of Educational Management and Policy and one from Measurement and Evaluation. Data obtained were analyzed using percentages and mean statistics. The findings indicate that students from educated parents achieve more than those from uneducated parents in academics; students from high-income status parents enjoy considerable advantage in academic performance than students of low income status parents. Based on the findings, the study recommended among others that parents should diversify their sources of income to be able to provide funds for their children’s schooling.